कुवलयानन्द : श्रीमदप्पय्यदीक्षितविरचित : (वृत्तिरहित:) Kuvalayananda of Appayya Dikshita (without vritti) : with the commentary Samanvaya in Sanskrit & English ; Part-1. - Ramachandra Aiyar,T K. (R S Vadhyar & Sons, 2018)
Part-1.